2022
DOI: 10.1002/epi4.12618
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal nocturnal seizure detection: Do we need to adapt algorithms for children?

Abstract: Objective: To assess the performance of a multimodal seizure detection device, first tested in adults (sensitivity 86%, PPV 49%), in a pediatric cohort living at home or residential care. Methods:In this multicenter, prospective, video-controlled cohort-study, nocturnal seizures were detected by heartrate and movement changes in children with epilepsy and intellectual disability. Participants with a history of >1 monthly major motor seizure wore Nightwatch bracelet at night for 3 months.Major seizures were def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…In a prospective phase 4 study, we demonstrated the good performance of a wearable multimodal device (NightWatch) for the detection of nocturnal major motor seizures (median sensitivity of 86% per person and median false alarm rate [FAR] of .25 per night) 14 . Subsequent validation of NightWatch in a pediatric cohort revealed higher FARs, with rates amounting to .2 per hour 15 . To improve performance, we adapted the algorithm and found that it could reduce FAR to levels close to that of adults while maintaining high sensitivity 15 …”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…In a prospective phase 4 study, we demonstrated the good performance of a wearable multimodal device (NightWatch) for the detection of nocturnal major motor seizures (median sensitivity of 86% per person and median false alarm rate [FAR] of .25 per night) 14 . Subsequent validation of NightWatch in a pediatric cohort revealed higher FARs, with rates amounting to .2 per hour 15 . To improve performance, we adapted the algorithm and found that it could reduce FAR to levels close to that of adults while maintaining high sensitivity 15 …”
Section: Introductionmentioning
confidence: 95%
“…The multimodal algorithm of NightWatch, based on photoplethysmography and accelerometry (ACC) data, is described in more detail in previous publications. 14,15 Heart rate (HR) values are determined and updated every second based on a 5-min average of past individual peak-to-peak intervals. The accelerometry sensor measures motion and position, where position represents the angle of the sensor with respect to the gravity vector.…”
Section: Seizure Detection Algorithmmentioning
confidence: 99%
See 3 more Smart Citations